2010
DOI: 10.1007/s11099-010-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Chill-induced inhibition of photosynthesis was alleviated by 24-epibrassinolide pretreatment in cucumber during chilling and subsequent recovery

Abstract: To investigate whether brassinosteroids (BRs) could be used to alleviate chill-induced inhibition of photosynthesis in cucumber (Cucumis sativus L) during chilling and subsequent recovery, the effects of exogenously applied 24-epibrassinolide (EBR) on gas exchange, chlorophyll fluorescence parameters, and antioxidant enzyme activity were studied. Cucumber plants were exposed to chilling under low light (12/8 o C and 100 μmol m -2 s -1 PPFD) for 3 days and then recovered under normal temperature and high irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 45 publications
7
46
1
Order By: Relevance
“…Cold exposure can destroy the membrane structure because of lipid peroxidation, so an increase of MDA has been considered a marker for chilling injury. It has been demonstrated that lipid peroxidation and MDA content induced by cold stress can be suppressed by EBR treatment in cucumber and eggplant plants (Hu et al 2010;Wu et al 2014). In this study, the increase of MDA content in the controls progressed rapidly within the first 5 d of storage and then maintained constant.…”
Section: Electrolyte Leakage and Mda Contentmentioning
confidence: 47%
See 1 more Smart Citation
“…Cold exposure can destroy the membrane structure because of lipid peroxidation, so an increase of MDA has been considered a marker for chilling injury. It has been demonstrated that lipid peroxidation and MDA content induced by cold stress can be suppressed by EBR treatment in cucumber and eggplant plants (Hu et al 2010;Wu et al 2014). In this study, the increase of MDA content in the controls progressed rapidly within the first 5 d of storage and then maintained constant.…”
Section: Electrolyte Leakage and Mda Contentmentioning
confidence: 47%
“…In addition, treatment with exogenous brassinolide increased resistance of green bell pepper fruit to low temperature stress through a mechanism that improves the activity of antioxidant enzymes . 24-Epibrassinolide (EBR) is one of the most active forms of BRs available commercially, and has a favorable safety profile (Kuzmitsky and Mizulo 1991;Malikova et al 2008;Hu et al 2010). The use of EBR to enhance tolerance of eggplant seedlings to salt and cold stresses has been demonstrated (Wu et al 2014;Ding et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant enzymes including SOD, CAT and POX are the most efficient protective mechanisms against oxidative stress (Senaratna et al 2000;Kang et al 2003;Patykowski and Urbanek, 2003;Hu et al 2010). They control the level of ROS and eliminate their detrimental effects.…”
Section: Effects Of Cold and Sa + Cold On Antioxidant Enzyme Activitiesmentioning
confidence: 99%
“…The defence mechanisms against cold stress are quite complicated as both biochemical and physiological; however, it is well known that one of the most important among them is the antioxidative system. Because, similar to other stresses, reactive oxygen species (ROS) such as superoxide anion (O − 2 ), CONTACT Salih Mutlu salihmutlu@yahoo.com H 2 O 2 and hydroxyl radicals ( · OH) are produced during response to cold stress (Mutlu et al 2009a(Mutlu et al , 2009bHu et al 2010). Toxic levels of ROS can impair membrane permeability (Dias et al 2011) by inducing lipid peroxidation (Mutlu et al 2011;Esim et al 2014), cause damage to DNA and proteins (Bertrand et al 2011;Kekec et al 2013) and ultimately lead to programmed cell death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation